Impact of protein source and vitamin stability on broiler performance - Frempong, Nana Serwah (Kansas State University, 2018)
A study was carried out to determine the effect of replacing fish meal with either soybean meal or poultry by-product meal on broiler performance and total feed cost per kg of gain. A second study evaluated the effect of storage time and trace minerals on the stability of vitamins stored at high temperature and relative humidity and their subsequent effects on broiler performance, bone strength and ash. A third study consisting of two experiments was conducted to determine the effects of particle size, diet, method of analysis (laboratory, ground and unground) and feed form (mash and pellet) on the crude protein predictability of the near infrared reflectance spectroscopy while using standard calibrations installed with the instrument. In study 1, three dietary treatments, 1) SBM-FM diet, 2) SBM diet and 3) SBM-PBM diet, were allocated to 36 pens using a completely randomized design with 12 replicates per treatment. Replacing FM with SBM and PBM in broiler diets improved growth performance and reduced total feed cost per kg of gain. In study 2, seven experimental treatments, 1) 0 d VP, 2) 30 d VTMP, 3) 30 d VP, 4) 60 d VTMP, 5) 60 d VP, 6) 90 d VTMP and 7) 90 d VP, were stored for 0, 30, 60 and 90 days, respectively in an environmentally controlled chamber at 29.4°C and 75%. Samples of treatments were analyzed, and loss of vitamin activity was calculated after storage. Treatments were added to broiler diets to determine the effect of loss of vitamin activity on broiler performance. Dietary treatments were set up as randomized complete block design in four batteries. Storing vitamins with trace minerals for 90 days increased loss of vitamin activity as compared to when stored as vitamin premix. Loss of vitamin activity did not significantly affect overall broiler performance, bone strength and ash. In study 3, Exp. 1 was a 3 × 3 × 4 factorial with corn particles size (400, 600 and 800 μm), method of analysis (laboratory, unground and ground) and diet (SD, SFD, SFB and SB). Diets were formulated to contain 20% crude protein. Subsamples were ground through a 0.5 mm sieve. Crude protein contents of ground and unground samples were analyzed using the Foss DS2500 NIRS (Model Foss DS2500 Monochromator, Foss NIRSystems, Laurel, MD) and compared to laboratory results from wet chemistry analysis. Interaction (P≤0.05) was observed between diet and method and particle size and method, but similar (P≥0.05) crude protein was observed for particle size. Diets and particle sizes were significantly different (P≤0.05) as unground samples but no differences (P≥0.05) were observed when ground and analyzed using the NIRS or wet chemistry. Exp. 2 was a 3 ×2 factorial with method of analysis (laboratory, unground and ground) and feed form (mash and pellet). Diets were formulated to contain 20% crude protein and manufactured with 600 μm corn particle size. Portions of diets were pelleted using a pellet mill and cooled. Ground and unground mash and pellets were analyzed as in Exp. 1. Interaction was found (P≤0.05) between feed form and method of analysis. Feed form and method of analysis significantly (P≤0.05) affected crude protein prediction from the NIRS. Crude protein content of ground mash and pellets were similar (P≥0.05) to that of laboratory results. Generally, analyzing finished feed samples in the unground form with the NIRS while using standard calibrations yielded less accurate predictions for crude protein, but samples in the ground form yielded similar (P≥0.05) results when analyzed with either the NIRS or wet chemistry.
Keywords: Vitamin stability; Near Infrared Reflectance SpectroscopyProtein sources